Pengaruh Kompres Hangat Terhadap Dismenore saat Menstruasi pada Siswa Puteri Klas XI SMK N. 8 - Mastaida Tambun; Martaulina Sinaga (Yayasan Literasi Sains Indonesia, 2022)
Menstrual pain is one of the most common gynecological problems, affecting more than 50% of women and causing the inability to perform daily activities for 1 to 3 days each month in about 10% of these women. Giving a warm compress is an independent action. The warm effect of the compress can cause vasodilation in the blood vessels which will increase blood flow to the tissue, the distribution of acids and nutrients to the cells is enlarged and removed from the repaired substances which can reduce the primary menstrual pain caused by the blood supply to the endometrium. less (Natali, 2013). This warm compress is very effective in reducing menstrual pain. Based on an initial survey conducted by researchers at the SMK N. Padang Bulan Medan at school that there are still many students who experience dysmenorrhea during menstruation, and the researchers also conducted interviews with 10 students who felt dysmenorrhea during menstruation, the researcher asked if they had ever applied warm compresses, there were 5 people who had experienced it. do a warm compress. This study uses an analytical survey method with a Cross Sectional approach, the study was conducted at SMK N. Padang Bulan Medan, when this research will be conducted from February to July 2021, the population in this study is all female students of SMK N. Padang Bulan Medan class XI, the type of data used is primary data. , secondary and tertiary. While the data analysis used univariate and bivariate. The results showed that the majority of warm compresses did not apply warm compresses, namely 22 people (61.1%) in SMK N. Padang Bulan Medan students, Based on Dismonero the majority of SMK N. Padang Bulan Medan students experienced (Yes) as many as 20 people (55.6%), There is a relationship between compresses warm with Dismonero on students ofPuteri SMK N.8 Padang Bulan Tahun 2022 in 2021 with pvalue = 0.000.